Bioassessment of Water Quality of Mountainous Streams under Different Land Uses in Solan District of Himachal Pradesh, India - Chauhan, Aakriti; Verma, S. C.; Thakur, Meena (International Journal of Bio-resource and Stress Management, 2023)
Investigations were carried out in the Environmental Biology Laboratory of Department of Environmental Science, Dr Y S Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh, India during 2011-2012. Aquatic insects fauna were sampled from mountaineous streams of Kandaghat block situated in Solan district under different land uses (agriculture, forest and urban) seasons (rainy, winter and summer). The sampled aquatic insects were identified upto family level by using aquatic insect identification keys with help of stereoscopic binocular microscope. A total of 80 individuals m-2 and 59 individuals m-2 of aquatic insects were recorded under agriculture and urban land uses, respectively. Among all the land uses, forest land use recorded highest aquatic insects (107 m-2). Maximum aquatic insects (123 m-2) was during summer season with simpson’s biodiversity index of 0.01, whereas agriculture land use (0.11) was highest under different land uses. Maximum diversity of insects indicated less disturbance of the streams. EPT (Ephemeroptera, Plecoptera and Coleoptera) index for agriculture, urban and forest land uses was 3.46, 3.70 and 3.56, respectively. Percentage of individuals of Trichoptera in water bodies under agriculture, Urban and Forest land use were 12.60, 10.98 and 10.16%, respectively. Hemiptera were maximum (7.31%) under forest land use and minimum in Urban land use (2.03%), whereas order Odonata were maximum under Forest land use (9.31%) followed by urban (5.69%) and agriculture land use (4.47%). This indicated that aquatic insect fauna showed variation in distribution and abundance as well as biotic indices in mountainous streams under different land uses thereby reflecting good water quality.